PENGARUH SHOW AND TELL TERHADAP PERCAYA DIRI ANAK 4-5 TAHUN DI TK PEMBINA TEBAS - Irtia, Fitri; Ali, Muhamad; Yuniarni, Desni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe Purpose of this research is to know about the differentciation of children confidence before using show and tell method and knowing the confidence differencitation before and after using show and tell method and knowing the confidence differenciation before and after using show and tell method. This kind of research is experimental research method with one-group pretest-posttest design. The data experiment full filled with observation and documentation. The sample of this research is 4-5 years old children. Based on data analysis the research result titled The Effect Of The Show And Tell Method On Self Confidence in Childern Aged 4-5 Years In The Nursery Kindergartens TK Negeri Pembina Kecamatan Tebas is totally significant, because for the pretest score average is 17,7, and the posttest average is 10,60. And then the result from the table (8.271>2.0518) it means that there has after threatment given. Then to know how big the show and tell method the self confidence it has done ?effect size? test. With score1.648>1.00 knew that the effect from show and tell method to the self confidence of children ages 4-5 was.Keywords : Show and Tell method, self confidence, childern ages 4-5